Biotechnological strategies for the treatment of gluten intolerance - Rossi, Mauro (Academic Press, 2021)
Biotechnological Strategies for the Treatment of Gluten Intolerance provides a comprehensive overview of a wide range of biotechnological approaches that will further research and upon implementation improve the quality of life of this population. Gluten intolerance is a heterogeneous condition with varying levels of sensitivity that have typically been treated with a gluten free diet, but this book provides new and exciting biotechnological approaches that affect diet as well as non-dietary approaches. The reference describes the varying levels of sensitivity and explores symptoms beyond the intestines for a complete overview of the spectrum of sensitivity. The impact of diversity of wheat species, gluten quality and the nutritional values of gluten free products are extensively discussed. This reference is perfect for researchers and clinicians that want to further treatment options for those suffering from gluten sensitivity.